Pengaruh Work Life Balance dan Lingkungan Kerja Non Fisik terhadap Loyalitas Karyawan pada Generasi Milenial - Muhammad Fajri Mauludi; Kustini Kustini (J-MAS (Jurnal Manajemen dan Sains), 2022)
The purpose of this study was to determine whether the variable Work Life Balance and non-physical work environment affect the loyalty of millennial generation employees in Banyuwangi Regency. The primary data used in this study was obtained through distributing questionnaires to the targeted respondents, namely the millennial generation with a minimum age of 21 years and a maximum of 40 years. This study observes the loyalty of millennial generation employees in Banyuwangi Regency. This study uses quantitative analysis to determine the value of respondents' responses to the variables used in the study, using SmartPLS software. The results of this study succeeded in proving that work life balance and non-physical work environment have a significant positive relationship to employee loyalty in Banyuwangi Regency.